Hierarchical transcriptional network governing heterogeneous T cell exhaustion and its implications for immune checkpoint blockade - Tian, Weihong; Qin, Gaofeng; Jia, Miaomiao; Li, Wuhao; Cai, Weili; Wang, Hui; Zhao, Yangjing; Bao, Xuanwen; Wei, Wangzhi; Zhang, Yu; Shao, Qixiang (Frontiers in Immunology, 2023)
The fundamental principle of immune checkpoint blockade (ICB) is to protect tumor-infiltrating T cells from being exhausted. Despite the remarkable success achieved by ICB treatment, only a small group of patients benefit from it. Characterized by a hypofunctional state with the expression of multiple inhibitory receptors, exhausted T (Tex) cells are a major obstacle in improving ICB. T cell exhaustion is a progressive process which adapts to persistent antigen stimulation in chronic infections and cancers. In this review, we elucidate the heterogeneity of Tex cells and offer new insights into the hierarchical transcriptional regulation of T cell exhaustion. Factors and signaling pathways that induce and promote exhaustion are also summarized. Moreover, we review the epigenetic and metabolic alterations of Tex cells and discuss how PD-1 signaling affects the balance between T cell activation and exhaustion, aiming to provide more therapeutic targets for applications of combinational immunotherapies.